Suboptimal Omega-3 Levels in Australian Adolescents - Grant, Ross; Guest, Jade; Bilgin, Ayse; Morris, Margaret J.; Garg, Manohar; Pearce, Robyn (International Journal of Child Health and Nutrition, 2013)
Objective: To quantitate the omega-3 status in a cohort of Australian adolescents. Design, Setting and Participants: A cross-sectional descriptive study of 251 apparently healthy adolescents (192 female, 59 male) aged 15-17 years, in year 11, from 10 schools within the Northern Sydney and Central Coast areas of New South Wales. Participants provided a morning non-fasting blood sample via finger-prick and written answers to specific demographic and lifestyle questions. Omega-3 index was calculated by adding %EPA and %DHA values in the whole blood. Equivalent erythrocyte omega-3 index values were obtained by using conversion factors (1.33 for EPA and 2.22 for DHA) from published erythrocyte/whole blood values. Main Outcome Measures: Quantitation of the individual, and estimation of the group average, blood omega-3 Index. Results: The blood omega-3 Index for this adolescent cohort ranged from 2.1-22.3 with a mean of 8.3±3.2, and median of 7.8. On average males had a higher omega-3 Index compared to females (10.5±3.7 vs 7.7±2.6, p<0.001). Fifty three percent of adolescents tested had an omega-3 Index below the optimum of >8. Three percent had an Index of <4, placing them in the high risk category for disease. On average, adolescents from low or medium socioeconomic communities had a significantly lower omega-3 Index compared to those from higher socioeconomic neighbourhoods (mean difference=1.4, p=0.018). Overall 20% of boys and 17% of girls reported regularly taking omega-3 supplements. Regular use of omega-3 supplements was associated with a higher average omega-3 Index (9.8±3.7, n=44 compared to 8.0±3.0, n=203, p=0.001 in those not taking supplements). Conclusion: This study indicates that Australian adolescents, even when from advantaged homes, have a high probability of below optimum omega-3 levels. As reduced omega-3 levels are linked to conditions of public health concern such as diabetes, asthma and depression, targeted strategies to improve the omega-3 status in the childhood population may be warranted.